Sinergitas Penegakan Hukum Terpadu dalam Mengeliminasi Pelanggaran Pilkada di Kabupaten Merauke - Koagouw, Jerry; Silo, Akbar; Muhdiarta, Untung; Aedah, Nur (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2023)
This study aims to analyze the Synergy of Integrated Law Enforcement in Eliminating Mal Pilkada Practices in Merauke Regency. The research method used is descriptive qualitative. The research location is in Merauke Regency. The technique for determining informants was selected by appointing 5 people as key informants from the KPU, Bawaslu, Merauke Police and the Merauke State Prosecutor's Office and the Regional Government. The data collection used included interviews, observations, FGDs and document studies. Data analysis techniques include the stages of data reduction, data presentation, data interpretation and drawing conclusions. The results of the study show that the synergy of integrated law enforcement in eliminating malpractice regional elections in Merauke Regency at the implementation level is less effective. The integrated law enforcement integrated model is deemed necessary to use the concept of collaborative governance which is considered relevant to describe the collaboration and cooperation that must be carried out by Gakkumdu at the Pilkada stage.